Enhancing Mother’s Knowledge about Preventing Stunting in Toddlers through Counseling on the Use of Local Food Ingredients - Fathmawati Fathmawati; Yulia Yulia; Ayu Rafiony (Institute for Research and Community Services, 2022)
Stunting has been a problem in Sendoyan Village, with its prevalence rate exceeding 30%. Nevertheless, handling stunting is not easy in that it requires an integrated approach, including how to increase the knowledge of mothers and families about stunting. This community service aimed to enhance the knowledge of mothers with stunted children regarding their parental roles and the proper disposal of feces. The program commenced with initial surveys and counseling at the posyandu (pos pelayanan terpadu), followed by several home visits involving health cadres. The preliminary findings showed that mothers with stunted toddlers were not able to choose the proper food for their toddlers and that there were still families who did not defecate in proper places. The counseling at the posyandu appeared to benefit the participating mothers even though they had to juggle with their responsibility of caring for their toddlers. Accordingly, the home visits, when conducted properly, could be an effective way to deliver the knowledge to the mothers. The public health centers (puskesmas) should also equip the health cadres with sufficient knowledge in childcare, making them ready to transfer the knowledge in stunting prevention to the mothers.